Identifying factors of financial exclusion of rural farmers: case study in Ulu Dong, Raub, Pahang - Shaharuddin, Siti Saffa’; Arifin, Aziq; Hafiz, Abdullah; Redzuan, Nur Harena (Springer, 2023)
Islamic microfinance services and products are not new topics that help in financial inclusion. Low-income groups benefit the most from the services and products to maintain their activities or business to generate an income. The business can be in various forms such as sales, food, and beverages or the agricultural and fisheries sector. However, even with the services and products of Islamic microfinance, it is found that there is an exclusion for the rural areas in the financial system. Therefore, this study narrows down its research to a subdistrict of Raub named Ulu Dong in Pahang to identify the factors of exclusion of the rural farmers in the areas. With qualitative methodology through library research and interview, this research concludes their findings at the end. The result of this study shows that there are several issues and challenges that hampered rural farmers in Ulu Dong, Raub, Pahang to take into serious consideration.